Silico-Aluminophosphate and Alkali-Aluminosilicate Geopolymers: A Comparative Review - Wang, Yan-Shuai; Alrefaei, Yazan; Dai, Jian-Guo (Frontiers in Materials, 2019)
Chemically activated materials (often termed as geopolymer) have received attracting attentions in civil, material and environmental research fields as a toolkit alternative to traditional Portland cement in specific applications. This paper presents a state-of-the-art review on silico-aluminophosphate (SAP) geopolymers in terms of definition, chemistries involved during geopolymerization, mechanical and durability performance, environmental impacts, and their potentials in applications as compared to conventional alkali-aluminosilicate (AAS) geopolymers. Recommendations for future applications are also highlighted. It is found that S-A-P gels with six-coordinated aluminum environment dominate in SAP geopolymers, while the aluminum in N-A-S-H gels formed in the AAS geopolymers is characterized by four-coordinated features. Besides, the slow performance development of SAP geopolymer matrix under ambient temperature curing can be compensated through incorporating additional countermeasures (e.g., metal sources) which allow the tailored design of such geopolymers for certain in-situ applications, i.e., calcium-bearing C-(A)-S-H gels co-existed with N-A-S-H gels are dominant in AAS geopolymers, while S-A-P gels enhanced by phosphate-containing crystalline/amorphous phases are the main products in SAP geopolymers. Another advantage of SAP geopolymers is their environmental friendliness relative to the AAS geopolymers due to the utilization of phosphate activators that require lower production energy relative to silicate-containing activators. However, the higher cost of phosphate activators may confine the applications of SAP geopolymers in some exquisite or special fields.